Using appreciative inquiry to empower international students to flourish in research - Hung, Lillian; Chan, Stephen Cheong Yu; Ren, Lily Haopu; Ito, Hiro; Chakraborty, Bubli (Journal of International Students, 2024)
Despite growing studies on Appreciative Inquiry (AI), rooted in positive psychology, its application in a research laboratory and its associated impact on students’ mental health and well-being are underexplored. Thus, this study explores how a positive environment affects students’ mental health and well-being. Interpretive descriptions guided the data collection and analysis process. We conducted focus groups and interviews with 23 students recruited through convenience sampling. Reflexive thematic analysis identified three themes: (1) feeling valued by others builds confidence, (2) strength-based guidance fosters growth, and (3) meaningful research work increases resilience. Our study suggests that a positive environment informed by Appreciative Inquiry has the potential to positively affect the mental health and well-being of international students.